Moral Hazard and Medical Assessment - Duncan, Grant (Victoria University of Wellington Law Review, 2003)
Across its history ACC policy on rehabilitation has fluctuated, as has the approach to compensating victims with partial but permanent incapacity. These procedures offer an important window onto shifting ACC attitudes to entitlements, social equity, and cost control, which accompanied the legislative changes of the 1990s. This paper examines the particular methods used by ACC in recent years to assess the capacity of beneficiaries to return to work, as well as methods used to calculate benefits for partial long-term incapacity. The paper argues that these ACC practices reveal the changing strategic relationship between beneficiaries and a cost-conscious state authority.